The Concept of Puberty in Islamic Education: A Philosophical Review of the Transition of Adolescents to Adults - Alya Diva Juniardi; Nasikhin; Mustopa; Ali Imron (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
This study aims to analyze the understanding of the concept of puberty (adulthood) in Islamic education and its implications for the development of educational practices and the formation of adolescent character. Through a qualitative approach with the literature research method, data is collected from sources such as the Qur'an, Hadith, and related literature, then analyzed using content analysis. The results show that puberty is not just a biological change, but a critical phase for moral and spiritual growth, so it requires structured education to prepare adolescents for religious and social responsibilities. The study concludes that integrating a philosophical understanding of puberty into Islamic education can contribute significantly to the holistic development of adolescents, equipping them with the values and skills needed to navigate the complexities of modern life. This study advocates a deeper engagement with the concept of puberty to cultivate responsible and moral individuals in society.